Primer-dependent synthesis of covalently linked dimeric RNA molecules by poliovirus replicase. - Lubinski, J M (1987)
Poliovirus-specific RNA-dependent RNA polymerase (replicase, 3Dpol) was purified from HeLa cells infected with poliovirus. The purified enzyme preparation contained two proteins of apparent molecular weights 63,000 and 35,000. The 63,000-Mr polypeptide was virus-specific RNA-dependent RNA polymerase, and the 35,000-Mr polypeptide was of host origin. Both polypeptides copurified through five column chromatographic steps. The purified enzyme preparation catalyzed synthesis of covalently linked dimeric RNA products from a poliovirion RNA template. This reaction was absolutely dependent on added oligo(U) primer, and the dimeric product appeared to be made of both plus- and minus-strand RNA molecules. Experiments with 5' [32P]oligo(U) primer and all four unlabeled nucleotides suggest that the viral replicase elongates the primer, copying the poliovirion RNA template (plus strand), and the newly synthesized minus strand snaps back on itself to generate a template-primer structure which is elongated by the replicase to form covalently linked dimeric RNA molecules. Kinetic studies showed that a partially purified preparation of poliovirus replicase contains a nuclease which can cleave the covalently linked dimeric RNA molecules, generating template-length RNA products.